2023
DOI: 10.2991/978-2-38476-032-9_32
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Work Values on Readiness to Change in Employees

Abstract: Employee readiness is very important and positively impacts change and the organization. Various factors can affect employee readiness to change, including work values. This study aims to determine work values' role in the readiness to change in employees in a company organization. The research method is carried out by studying literature. Collecting data by looking for theoretical references relevant to work values' role on employee readiness to change. The results of this study show that work values have a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…First, both Gen X and Y showed that the work value variable positively affects work attitude. These results are in line with the research from Chen and Lee (2021), Hendayani (2020), Mat Ali and Aisyah Panatik (2013), and Shofiya et al (2023 who state that there is a positive correlation between work values and work attitudes. The more management emphasizes work values, the better the work attitudes of these two generations.…”
Section: Discussionsupporting
confidence: 91%
“…First, both Gen X and Y showed that the work value variable positively affects work attitude. These results are in line with the research from Chen and Lee (2021), Hendayani (2020), Mat Ali and Aisyah Panatik (2013), and Shofiya et al (2023 who state that there is a positive correlation between work values and work attitudes. The more management emphasizes work values, the better the work attitudes of these two generations.…”
Section: Discussionsupporting
confidence: 91%